On art, artists, Latin America, and other utopias - Camnitzer, Luis, 1937- (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2009)
Artist, educator, curator, and critic Luis Camnitzer has been writing about contemporary art ever since he left his native Uruguay in 1964 for a fellowship in New York City. As a transplant from the "periphery" to the "center," Camnitzer has had to confront fundamental questions about making art in the Americas, asking himself and others: What is "Latin American art"? How does it relate (if it does) to art created in the centers of New York and Europe? What is the role of the artist in exile? Writing about issues of such personal, cultural, and indeed political import has long been an integral part of Camnitzer's artistic project, a way of developing an idiosyncratic art history in which to work out his own place in the picture. This volume gathers Camnitzer's most thought-provoking essays--"texts written to make something happen," in the words of volume editor Rachel Weiss. They elaborate themes that appear persistently throughout Camnitzer's work: art world systems versus an art of commitment; artistic genealogies and how they are consecrated; and, most insistently, the possibilities for artistic agency. The theme of "translation" informs the texts in the first part of the book, with Camnitzer asking such questions as "What is Latin America, and who asks the question? Who is the artist, there and here?" The texts in the second section are more historically than geographically oriented, exploring little-known moments, works, and events that compose the legacy that Camnitzer draws on and offers to his readers.